Clinical Predictors of Relapse in a Cohort of Steroid-Treated Patients With Well-Controlled Myasthenia Gravis - Su, Shengyao; Lei, Lin; Fan, Zhirong; Zhang, Shu; Wen, Qi; Wang, Jingsi; Lu, Yan; Di, Li; Wang, Min; Chen, Hai; Da, Yuwei (Frontiers in Neurology, 2022)
Objective Despite the high efficiency of glucocorticoids (GCs), ~18–34% patients with myasthenia gravis (MG) may experience relapses of the disease. Here, we aim to identify clinical factors related to relapses during steroid tapering or after withdrawal in MG patients who were well-managed on steroid monotherapy. Methods We conducted a retrospective study on 125 MG patients from the Xuanwu Hospital MG Trial Database. Patients were treated with corticosteroids and achieved minimal manifestation status (MMS) or better. Patients were divided into steroid reduction subset (N = 74) and steroid withdrawal subset (N = 51). Clinical characteristics and therapeutic data were compared between patients with disease relapse and those who maintained clinical remission at the last follow-ups. Cox proportional hazards regression models were used to identify risk factors of relapse in each subset. Results Thirty-seven (29.6%) patients experienced relapses during the follow-up periods. Relapse during the steroid reduction was significantly associated with drug reducing duration (HR = 0.81, 95%CI 0.74–0.89, P < 0.001). Risk of relapse was augmented if the drug reducing duration was <11.5 months (HR 27.80, 95%CI 5.88–131.57, P < 0.001). Among patients who discontinued the steroids, those with onset symptoms of bulbar weakness (adjusted HR 3.59, 95%CI 1.19–10.81, P = 0.023) were more likely to experience relapse. Conclusion Our study demonstrated that patients could benefit from prolonged steroid-reducing duration to prevent disease relapse. Patients with bulbar weakness at disease onset should be proposed to take long-term steroids or other immunosuppressants.